The Antarctic Peninsula: Argentina and Chile in the era of global change - Vidal, Florian (The Polar Journal, 2023)
While Argentine-Chilean relations have long been swayed between cooperation and confrontation since their independence in the 19th century and a long-standing presence in Antarctica, the stretch between Tierra del Fuego to the Antarctic Peninsula stands as the closest lane (i.e. about 1,000 km) to any other continent. Despite their territorial dispute over islands on the fractured southern tip of South America and territorial claims on the Antarctic, their common diplo-matic ground successfully defuses any potential geopolitical instability. Along with Chile and Argentina, British claims overlap in the Antarctic Peninsula, which establishes unique geopolitical conditions in the whole of Antarctica. In this context, scientific missions and growing tourist activities could transform the region into the Antarctic gateway. From potential mineral resources exploitation to the United States- China global competition, the South Atlantic area could become a strategic bridgehead in light of the brewing geopolitical shift during the 21st century. Considering that climate change and geostrategic conditions evolve somewhat quickly to transform the Western Antarctic area, this article aims to assess and comprehend how these external drivers may affect the two South American countries. Given the fact that Antarctica is part of their respective national narrative, how do Argentina and Chile intend to maintain their presence and protect their interest in these shifting conditions? What are the vectors for partnering with the world’s great powers, such as China? Ultimately, could this space become a choke point through the 21st century?
Keywords: Antarktis; geopolitikk; politikk; ressurser

Four principles to justify claims to jurisdiction and to natural resources in Antarctica - Mancilla, Alejandra (Yearbook of Polar Law, 2020)
Global pressure over Antarctic resources will mount in the course of the coming decades. Three factors are likely to motivate states to claim jurisdictional rights or rights to natural resources in Antarctica: climate change, dwindling natural resources in the rest of the world, and the fact that – by virtue of Article IV of the Antarctic Treaty – the question of sovereignty remains unresolved. It is high time to think about the moral dimensions that should shape Antarctic claims in the future. Is there any state or group of states more entitled than others to make such claims? What does sound management of natural resources require? How should environmental concerns factor into decisions about jurisdictional control and appropriation of natural resources? With these broad questions in the background, in this article I examine four principles of justice that figure prominently in current theories of territorial rights and rights over natural resources in political philosophy: connection, capacity, fair distribution, and need. I show how these principles have been used by states, alone or in tandem, to justify claims to jurisdiction and claims to natural resources in Antarctica. After pointing to their main strengths and weaknesses, I suggest that they may be necessary, but insufficient to build a just framework for jurisdiction and appropriation of resources in the White Continent.
Keywords: Antarktis; jus; politikk; ressurser

The moral limits of territorial claims in Antarctica - Mancilla, Alejandra (Ethics & International Affairs, 2018)
By virtue of the Antarctic Treaty, signed in 1959, the territorial claims to Antarctica of seven of the original signatories were held in abeyance or “frozen.” Considered by many as an exemplar of international law, the Antarctic Treaty System has come to be increasingly questioned, however, in a very much changed global scenario that presents new challenges to the governance of the White Continent. In this context, it is necessary to gain a clearer understanding of the moral weight of those initial claims, which stand (despite being frozen) as a cornerstone of the treaty. The aim of this article is to offer an appraisal of such claims, which may be divided into two main kinds: those grounded on some relevant link to the territory, and those grounded on official documents and geographical doctrines. After pointing to the limitations and challenges that they face, I conclude with some remarks about how this assessment ought to serve as a starting point to rethink the territorial status of Antarctica.
Keywords: Antarktis; historie; jus; politikk; ressurser

The ANTOSTRAT Legacy: Science Collaboration and International Transparency in Potential Marine Mineral Resource Exploitation of Antarctica - Cooper, Alan; Barker, Peter; Barrett, Peter; Behrendt, John; Brancolini, Giuliano; Childs, Jonathan; Escutia, Carlota; Jokat, Wilfried; Kristoffersen, Yngve; Leitchenkov, German; Stagg, Howard; Tanahashi, Manabu; et al. (Science Diplomacy: Antarctica, Science, and the Governance of International Spaces, 2011)
Keywords: Antarktis; geopolitikk; internasjonal samarbeid; marin geologi; mineraler; ressurser; stratigrafi; tektonikk

Perspectives on the Economic History of the Antarctic Region - Basberg, Bjørn L (Discussion paper Norges handelshøyskole, Institutt for samfunnsøkonomi, 2006)
Keywords: Antarktis; ekspedisjoner; fiskeindustri; forskning; hvalfangst; ressurser; turisme; økonomi; økonomisk historie

Fiskerier i Antarktis (6.4) - Dommasnes, Are; Iversen, Svein A; Løbach, Terje (Havets ressurser 2004 (Fisken og havet : Særnummer), 2004)
Keywords: Antarktis; fangst; fiskeindustri; fiskeriforskning; krill; ressurser